Image De-noising using Un-decimated Wavelet Transform (UWT) with Soft Thresholding Technique - Golilarz, Noorbakhsh Amiri; Demirel, Hasan (IEEE, 2017)
Noise can affect an image in a negative way and it can destroy some important details and features of image as well, so we need to dispose the noise to retain significant characteristics of image. This noise removing is very useful in improving the visually of image which leads to improved analysis process. In this paper we introduced a new technique for image de-noising in wavelet domain which uses soft thresholding function. De-noising based on un-decimated wavelet transform (UWT) using soft threshold function results in acquiring better visual quality and PSNR values in comparison with alternative techniques in the field of image de-noising in wavelet domain.
9th International Conference on Computational Intelligence and Communication Networks (CICN) -- SEP 16-17, 2017 -- Final Int Univ, Girne, CYPRUS
Keywords: Noise removing; Wavelet domain; Soft thresholding